2021
DOI: 10.1186/s12876-021-01857-8
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of ethnic minority patients who are living with a primary chronic bowel condition: a systematic scoping review with narrative synthesis

Abstract: Background Prevalence of chronic gastrointestinal diseases has been rising amongst ethnic minority populations in Western countries, despite the first-generation migrants originating from countries of low prevalence. Differences caused by genetic, environmental, cultural, and religious factors in each context may contribute towards shaping experiences of ethnic minority individuals living with primary bowel conditions. This review aimed to explore the experiences of ethnic minority patients liv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
(283 reference statements)
0
2
0
Order By: Relevance
“…Other digestive conditions are poorly studied ( Parkman et al, 2019 ). Historically, studies have reported that White populations were more likely to experience IBS than other racial and ethnic groups, such as African American/Black populations ( Ahmed et al, 2021 ; Sandler, 1990 ; Wigington et al, 2005 ). However, empirical studies from 2016 to 2022 reveal that IBS is increasing among African American/Black populations ( Afzali & Cross, 2016 ; Ahmed et al, 2021 ; Aniwan et al, 2019 ; Anyane-Yeboa et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other digestive conditions are poorly studied ( Parkman et al, 2019 ). Historically, studies have reported that White populations were more likely to experience IBS than other racial and ethnic groups, such as African American/Black populations ( Ahmed et al, 2021 ; Sandler, 1990 ; Wigington et al, 2005 ). However, empirical studies from 2016 to 2022 reveal that IBS is increasing among African American/Black populations ( Afzali & Cross, 2016 ; Ahmed et al, 2021 ; Aniwan et al, 2019 ; Anyane-Yeboa et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, studies have reported that White populations were more likely to experience IBS than other racial and ethnic groups, such as African American/Black populations ( Ahmed et al, 2021 ; Sandler, 1990 ; Wigington et al, 2005 ). However, empirical studies from 2016 to 2022 reveal that IBS is increasing among African American/Black populations ( Afzali & Cross, 2016 ; Ahmed et al, 2021 ; Aniwan et al, 2019 ; Anyane-Yeboa et al, 2022 ). Another study indicated that African Americans and Black Americans have the highest rates for several cancers, including gastric and small bowel cancers ( Ashktorab et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%